Farmer Group Training in Utilizing Bokashi for Cultivating Vegetable Crops - Hayat, Edy Syafril; Andayani, Sri; Mulyadi, Mulyadi (STKIP Singkawang, 2024)
Suboptimal land use by farmers for crop cultivation activities faces obstacles including less fertile soil conditions, low soil pH and iron poisoning. To overcome this problem, efforts are needed to increase farmers' knowledge and skills, especially in the use of organic fertilizers, one of which is bokashi. The aim of this PKM activity is to increase the knowledge and skills of partners in using bokashi for plant cultivation. To achieve this goal, the method used in implementing this PKM activity is: 1). Counseling is carried out face to face with partner groups. Extension material regarding organic fertilizer, making and applying bokashi, cultivating leaf lettuce, and farmer group management; 2). Demonstration/practice of bokashi application on growing media 3). Mentoring, mentoring activities are carried out through visits to partner locations to see the results of bokashi practices that have been carried out, and holding discussions with partners. The problem with the production aspect in this farmer group is: the use of bokashi for cultivating vegetable crops is still not optimal. The solution offered to overcome production aspect problems is to transfer knowledge and technology for the use/application of bokashi for the cultivation of vegetable crops through the use of agricultural waste and available livestock materials to be used as substitutes/substitutes for inorganic fertilizers. Through the PKM activities that have been carried out, it can be seen that there has been an increase in participants' knowledge about bokashi from the initial condition of 36.63% to 94%.